THE USE OF TROPHIC DIATOM INDEX TO DETERMINE WATER QUALITY IN THE UPSTREAM OF CILEUNGSI RIVER, WEST JAVA - Nuralim Pasisingi; Niken TM Pratiwi; Majariana Krisanti (Research Center for Fisheries, 2014)
Human activities in the watershed in the upstream of Cileungsi river have tendency to bring high organic materials to the river which determines the aquatic condition of the river. The decreased water quality is event because of the organic materials in the upstream of Cileungsi river would bring negative impacts towards water condition in the downstream. This study was conducted in determining the water quality in the upstream of Cileungsi river, using Trophic Diatom Index (TDI). The sampling was taken in four different sites in the river and sub-river of the upstream of the river. The sampling of ephilitic diatom organisms were taken by scraping the surface of substrate rocks using brush then soaked the materials into a sampling bottle which hasbun containing destile water. Diatom density was measured using census method according to standard of APHA 2012. The TDI score ranged from 48.25 to 60.47, indicating that the water quality of upstream of Cileungsi river is classified from good until poor condition.